2010
DOI: 10.1186/1476-511x-9-102
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of apolipoprotein M in human colorectal tissues

Abstract: BackgroundIt has been well documented that apolipoprotein M (apoM) is principally expressed in the liver and kidney. However we found that there was weak apoM expression in other tissues or organs too, which could not be ignored. In the present study, we therefore examined apoM expression in human colorectal tissues including cancer tissues, cancer adjacent normal tissues, polyp tissues and normal mucosa as well as inflammatory mucosa.MethodsTissue samples were collected from patients who underwent surgical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 30 publications
1
27
1
Order By: Relevance
“…Overexpression of APOM inhibited the proliferation, migration, and invasion of hepatoma cells and the development of xenograft tumors in nude mice, and promoted apoptosis . APOM mRNA and protein levels were notably reduced in colorectal cancer tissues, compared to adjacent healthy tissues, normal mucosa, polyps, and inflammatory mucosa …”
Section: Apolipoproteins and Cancermentioning
confidence: 98%
“…Overexpression of APOM inhibited the proliferation, migration, and invasion of hepatoma cells and the development of xenograft tumors in nude mice, and promoted apoptosis . APOM mRNA and protein levels were notably reduced in colorectal cancer tissues, compared to adjacent healthy tissues, normal mucosa, polyps, and inflammatory mucosa …”
Section: Apolipoproteins and Cancermentioning
confidence: 98%
“…Human apoM is exclusively expressed in the hepatocytes in liver and tubular epithelial cell in kidney, and small amounts were also found in fetal liver and fetal kidney [2]. Luo, et al,[3] demonstrated that apoM could also be abundantly expressed in human colorectal tissues, although the pathophysiological importance of this expression and if it could influence plasma apoM pool are unknown. Wolfrum, et al, [4] demonstrated that apoM, by influencing preβ-HDL formation, being an important regulator of HDL metabolism in vivo, which could influence cholesterol efflux and the susceptibility of atherosclerosis.…”
mentioning
confidence: 99%
“…Human APOM is mainly found in hepatocytes of the liver and tubular epithelial cells in kidney [1], and it's also expressed weakly in the colorectal tissues [2]. It has been demonstrated that APOM is important for the formation of preβ-HDL and cholesterol efflux to HDL, which could attenuate atherosclerotic process [3].…”
Section: Introductionmentioning
confidence: 99%